2014
DOI: 10.1016/j.jalz.2014.05.581
|View full text |Cite
|
Sign up to set email alerts
|

P1‐340: Subjective Cognitive Complaints Contribute to Misdiagnosis of Mild Cognitive Impairment

Abstract: Subjective cognitive complaints are a criterion for the diagnosis of mild cognitive impairment (MCI), despite their uncertain relationship to objective memory performance in MCI. We aimed to examine self-reported cognitive complaints in subgroups of the Alzheimer's Disease Neuroimaging Initiative (ADNI) MCI cohort to determine whether they are a valuable inclusion in the diagnosis of MCI or, alternatively, if they contribute to misdiagnosis. Subgroups of MCI were derived using cluster analysis of baseline neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…Additionally, objective cognitive functioning and self-reported cognitive complaints were not associated, but there was a significant positive relationship between depressive symptoms and self-reported cognitive complaints. Overall, the authors concluded that reliance on self-reported cognitive complaints could lead to misdiagnosis of MCI [34]. We demonstrated that the potential for misdiagnosis of cognitive impairment could extend to OAE, and therefore, identifying alternative ways of screening for cognitive impairment may be important.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, objective cognitive functioning and self-reported cognitive complaints were not associated, but there was a significant positive relationship between depressive symptoms and self-reported cognitive complaints. Overall, the authors concluded that reliance on self-reported cognitive complaints could lead to misdiagnosis of MCI [34]. We demonstrated that the potential for misdiagnosis of cognitive impairment could extend to OAE, and therefore, identifying alternative ways of screening for cognitive impairment may be important.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, attention should be paid to whether observed changes in cognition associated with cancer therapies impact daily life functioning of patients. Although evidence suggests that performance on neuropsychological tests is related to aspects of everyday functioning, such as employment, medication adherence, and financial management, 92,114,115 none of the current studies on the potential effects of endocrine therapies evaluated these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies across a wide variety of patient populations with cognitive problems (such as multiple sclerosis, 89,90 traumatic brain injury, 91 mild cognitive impairment, 92 human immunodeficiency virus [HIV], 93 and cancer 94 ) have indicated that self-reported cognitive functions are an insufficient proxy for tested cognitive function, as they are generally weakly associated with tested cognitive function, and are more frequently and strongly associated with an individual's mood status. Thus, we exclusively included studies that used formal neuropsychological tests as the primary indicator of cognitive dysfunction.…”
Section: Neuropsychological Examinationsmentioning
confidence: 99%
“…First, we investigated individuals with MCI from the ADNI database, and previous studies have argued that there is a high rate of false-positive diagnosis of MCI in ADNI. 7,38 Nonetheless, we believe that the crucial measure is the discrepancy in estimation between participants and informants rather than the diagnosis of MCI. Second, we relied on the participant-informant discrepancy method, assuming that informants' estimates are more accurate than participants' estimates.…”
Section: Discussionmentioning
confidence: 95%
“…However, previous studies of the discrepancy between participant and informant estimates of decline have employed various different measures to calculate this discrepancy, including sample-specific cutoffs that are difficult to apply in the clinic. 7,9,10,13 For clinicians to use a discrepancy score routinely, they should be able to calculate it as simply and as intuitively as possible.…”
mentioning
confidence: 99%